The effect of a model presenting the subject of the object in the achievement of the fifth grade students in Arabic grammar - Rahmani, Isak; Sakbane Kazem, Mohamed (Journal of Human Sciences, 2023)
The study aims to identify (the effect of a model presenting the subject of the object in the achievement of the fifth grade students in the Arabic grammar subject). The study sample consisted of 107 students, distributed into two groups. The post-test was presented to a group of experts and specialists, then the post-test was applied in its final form to the research sample that he studied himself, and the results showed, using the t-test, that there was a statistically significant difference at the level of significance 0.05 between the mean scores of the students of the experimental and control groups in favor of students The experimental group who studied the effect of the object-object model on the achievement of fifth-grade students in Arabic grammar.